Sobre as possibilidades da impermanência: Fotografia e monumento - Lais Myrrha (2007)
Departing from Walter Benjamins and Roland Barthes photography theory, we will go through the constellation of themes that deals with the construction and permanence of monuments, memories and the values given to obejcts or images. Distance and absence, as thought by theseauthors, will be regarded as fundamental questions. Equal weight will be given to punctual analysis of some works from artists such as Nan Goldin, Christian Boltanski, Rosângela Rennó, Joseph Beuys, Rachel Whiteread, Susan Hiller, Félix González-Torres and On Kawara. In them we will try to detect strategies and allegories on the relation memory / oblivion. At the same time, well try to see these works as vehicles of reinsertion of the memento mori in contemporary capitalists societies that, paradoxically, tries to put away the idea of death, throwing themselves in an unstoppable consumism that postulates as dead everything that has just born.